2016
DOI: 10.1111/epi.13508
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy due to mutations in the mitochondrial polymerase gamma (POLG) gene: A clinical and molecular genetic review

Abstract: We performed a systematic review of the clinical, molecular, and biochemical features of polymerase gamma (POLG)-related epilepsy and current evidence on seizure management. Patients were identified from a combined electronic search of articles using Ovid Medline and Scopus databases, published from January 2000 to January 2015. Only patients with a confirmed genetic diagnosis of POLG mutations were considered. Seventy-two articles were included for analysis. We identified 128 pathogenic variants in 372 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 82 publications
3
79
1
3
Order By: Relevance
“…Similar findings were obtained in a systematic review of 229 patients with POLG-related epilepsy in whom seizure semiology had been reported; 49% had generalized status epilepticus, whereas 34% had focal motor status. 24…”
Section: Polg Diseasementioning
confidence: 99%
“…Similar findings were obtained in a systematic review of 229 patients with POLG-related epilepsy in whom seizure semiology had been reported; 49% had generalized status epilepticus, whereas 34% had focal motor status. 24…”
Section: Polg Diseasementioning
confidence: 99%
“…Mutations in POLG cause a spectrum of clinical phenotypes, including myoclonic epilepsy myopathy and sensory ataxia (MEMSA), ataxia neuropathy spectrum (ANS) and both dominant and recessive chronic progressive external ophthalmoplegia (CPEO) . POLG defects result in either mtDNA depletion or accumulation of mtDNA deletions, and in Alpers’ syndrome it is depletion of mtDNA which is responsible for the development of severe mitochondrial respiratory chain impairments, and consequent cellular dysfunction and cell death in brain and liver . Recent whole exome sequencing has identified other molecular genetic causes of Alpers’ syndrome, including pathogenic mutations in FARS2 which encodes phenylalanyl‐tRNA synthetase , NARS2 which encodes asparaginyl‐tRNA synthetase and PARS2 which encodes prolyl‐tRNA synthetase .…”
Section: Introductionmentioning
confidence: 99%
“…POLG‐related syndromes comprise a continuum of overlapping diseases, ranging from severe phenotypes, such as Alpers‐Huttenlocher syndrome, to milder forms, including progressive external ophthalmoplegia. These syndromes characteristically present with epilepsy (50%‐80% at disease onset) . Alpers‐Huttenlocher syndrome is associated with infantile‐onset refractory, focal or generalized epilepsy.…”
Section: Disorders Of Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…These syndromes characteristically present with epilepsy (50%-80% at disease onset). 198,199 Alpers-Huttenlocher syndrome is associated with infantile-onset refractory, focal or generalized epilepsy. Seizures are predominantly occipital, as in mitochondrial spinocerebellar ataxia and epilepsy caused by POLG mutations, and are characterized by ictal visual loss, nystagmus, visual hallucinations of flickering colored light, and dysmorphopsia.…”
Section: Polg-related Syndromesmentioning
confidence: 99%